Respuesta :

Answer:

(11 x - 20)/(x (x - 4)) = 11x-20/x^2-4x

Step-by-step explanation:

Simplify the following:

6/(x - 4) + 5/x

Put each term in 6/(x - 4) + 5/x over the common denominator x (x - 4): 6/(x - 4) + 5/x = (6 x)/((x - 4) x) + (5 (x - 4))/((x - 4) x):

(6 x)/(x (x - 4)) + (5 (x - 4))/(x (x - 4))

(6 x)/((x - 4) x) + (5 (x - 4))/((x - 4) x) = (6 x + 5 (x - 4))/((x - 4) x):

(6 x + 5 (x - 4))/(x (x - 4))

5 (x - 4) = 5 x - 20:

(5 x - 20 + 6 x)/(x (x - 4))

Grouping like terms, 6 x + 5 x - 20 = (6 x + 5 x) - 20:

((6 x + 5 x) - 20)/(x (x - 4))

6 x + 5 x = 11 x:

Answer: (11 x - 20)/(x (x - 4))